Biologia populacional de Mellita quinquiesperforata Leske (1778) (ECHINODERMATA: CLYPEASTEROIDA: MELLITIDAE) na praia da Taíba, Ceará, Brasil. - Dias, Ismália Cassandra Costa Maia (2008)
Population biology aspects of Mellita quinquiesperforata were studied in Taíba Beach, state of Ceará (03º30,125’S; 038º54,469’W) between June of 2006 and August of 2007. Wave height, period, temperature, salinity and granulometry were registered. Pluviosity data was obtained from Fundação Cearense de Meteorologia e Recursos Hídricos (FUNCEME). Cross-shore profile, Dimentionless Dean’s Parameter (Ω), Surf Scale Parameter (Σ), Beach Index (BI) and Relative Tidal Range (RTR) were calculated for the morphodynamic beach description. Animals were sampled using a dredge perpendicular to the beach, divided into two line-transects (0 – 30 m and 30 – 60 m distant from the wave washing-zone). Monthly, the gonads of 30 adults with width superior to 40 mm were removed for the reproductive cycle analyses, 20 for histological processing and 10 for Gonad Index (GI), respectively. The initial cells and the gonad development stages were characterized and the average of 100 oocytes were measured a month. GI means were tested through unifatorial analysis of variance (ANOVA). Individuals were divided in size classes of 20 mm amplitude. Values of spatial distribution were calculated using the mean density in the sampling line-transect, results were plotted using the software Sigma Plot® (10.0 version). Frequency class histograms of 5 mm (wide) were analyzed using software FISAT II (1.2.2 version) for determination of growth, recruitment and mortality. Spearman correlation analysis (STATISTICA® 6.0 version) compared environmental parameters with density and the gonad development stages. Salinity and pluviosity presented significant variations during the study period and average classification of the sediment was composed by fine sand. Dean’s parameter (Ω) and BI values classified the beach as intermediate, with topographic profile presenting differences during the study. The values of the surf scale parameter indicated a dissipation of waves and the RTR indicated the tidal action as the main modifier of the beach profile. Differences in the gonad colour could macroscopicaly classify gender; females presented lilac coloured gonad and males presented creamy coloured gonad. Germinative cells lineage and development patterns were similar, in general, to echinoids, with reproductive cicle characterized by the frequency of individuals in the nutrient reserve stage. In general, males and females presented synchronism in the gonadal development. The allocation of nutrients is related to the maintenance of the species in the surf-zone and the investment in the size of the females gamete. Organism densities presented significant differences (p < 0,01) along the study period; the month of november of 2006 presented highest density, characterizing the recruitment event. There were no significant differences in the organisms distribution along the transect-lines, although there is a tendency to separate juveniles from adults, where the former are nearest to the shoreline. Only 60 – 80 mm organisms were significantly more abundant in the transect-line 2 zone (30 – 60 m). It was observed a high growth rate and mortality for this species with longevity estimated in 2.36 years. Salinity was positively correlated with density, while pluviosity presented correlation with the gonad development stages. Results suggests that for Mellita quinquiesperforata the environmental factors are as important as the physiological demand.